Targeting senescent cells enhances adipogenesis and metabolic function in old age - Xu, Ming; Palmer, Allyson K; Ding, Husheng; Weivoda, Megan M; Pirtskhalava, Tamar; White, Thomas A; Sepe, Anna; Johnson, Kurt O; Stout, Michael B; Giorgadze, Nino; Jensen, Michael D; LeBrasseur, Nathan K; et al. (eLife, 2015)
Senescent cells accumulate in fat with aging. We previously found genetic clearance of senescent cells from progeroid INK-ATTAC mice prevents lipodystrophy. Here we show that primary human senescent fat progenitors secrete activin A and directly inhibit adipogenesis in non-senescent progenitors. Blocking activin A partially restored lipid accumulation and expression of key adipogenic markers in differentiating progenitors exposed to senescent cells. Mouse fat tissue activin A increased with aging. Clearing senescent cells from 18-month-old naturally-aged INK-ATTAC mice reduced circulating activin A, blunted fat loss, and enhanced adipogenic transcription factor expression within 3 weeks. JAK inhibitor suppressed senescent cell activin A production and blunted senescent cell-mediated inhibition of adipogenesis. Eight weeks-treatment with ruxolitinib, an FDA-approved JAK1/2 inhibitor, reduced circulating activin A, preserved fat mass, reduced lipotoxicity, and increased insulin sensitivity in 22-month-old mice. Our study indicates targeting senescent cells or their products may alleviate age-related dysfunction of progenitors, adipose tissue, and metabolism. The likelihood of developing metabolic diseases such as diabetes increases with age. This is, in part, because the cells within fat and other tissues become less sensitive to the hormone insulin as people and other animals get older. Also, the stem cells that give rise to new, insulin-responsive fat cells become dysfunctional with increasing age. This is related to the accumulation of “senescent” cells, which, unlike normal fat cell progenitors, release molecules that are toxic to nearby and distant cells. Xu, Palmer et al. have now investigated if senescent cells interfere with the activity of stem cells from human fat tissue, and if getting rid of these senescent cells might restore the normal activity and insulin responsiveness of aged fat tissue. The experiments revealed that human senescent fat cell progenitors release a protein called activin A, which impedes the normal function of stem cells and fat tissue. Additionally, older mice had higher levels of activin A in both their blood and fat tissue than young mice. Xu, Palmer et al. then analyzed older mice that had been engineered to have senescent fat cells that could be triggered to essentially kill themselves when the mice were treated with a drug. Eliminating the senescent cells from these mice led to lower levels of activin A and more fat tissue (due to improved stem cell capacity to become fully functional fat cells) that expressed genes required for insulin responsiveness. This showed that senescent cells are a cause of age-related fat tissue loss and metabolic disease in older mice. Next, Xu, Palmer et al. treated older mice with drugs called JAK inhibitors, which they found reduce the production of activin A by senescent cells isolated from fat tissue. After two months of treatment, the levels of activin A in the blood and in fat tissue were indeed reduced. The fat tissue in treated mice also showed fewer features associated with the development of diabetes than the fat tissue of untreated mice. As such, these results paralleled those after selectively eliminating the senescent cells. Together these findings suggest that JAK inhibitors or drugs (called senolytics) that selectively eliminate senescent cells may have clinical benefits in treating age-related conditions such as diabetes and stem cell dysfunction.